Saracen strongholds, 1100-1500 the central and eastern Islamic lands - Nicolle, David 1944- (Fortress (Osprey Publishing), 2009)
Covering fortifications as far apart as North Africa, Afghanistan and northern India, this volume focuses on the Islamic side of the conflict, highlighting the fortifications in use when the Crusaders sought to reconquer the Holy Land, as well as the eventual absorption of the territories of Byzantium into the Islamic world.